2021
DOI: 10.1007/s42114-021-00351-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium lignosulfonate on bonding strength and chemical structure of a lignosulfonate/chitosan-glutaraldehyde medium-density fiberboard adhesive

Abstract: Sodium lignosulfonate/chitosan-glutaraldehyde adhesive (L/C-G) has potential in environment-friendly wood-based panel adhesive applications. However, the effect of sodium lignosulfonate on the bonding strength and chemical structure of L/C-G was not elucidated. Herein, the role of sodium lignosulfonate in L/C-G was studied in detail by characterizing the mechanical properties and water resistance of medium-density fiberboards (MDFs) prepared using L/C-G as adhesives. The functional groups, thermal stability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…3(a and b)) clearly showed that the peaks at 3200–3450 cm −1 (hydroxyl and amino) and 1590 cm −1 (–NH bending vibration) significantly decreased, suggesting that reactions between the amino groups of the crosslinker and the hydroxyl groups of the lignin occurred. Meanwhile, the peaks at 1089 cm −1 were attributed to the increase in the ether bonds, 50 due to condensation reactions between lignin molecules. 51 In the XPS analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(a and b)) clearly showed that the peaks at 3200–3450 cm −1 (hydroxyl and amino) and 1590 cm −1 (–NH bending vibration) significantly decreased, suggesting that reactions between the amino groups of the crosslinker and the hydroxyl groups of the lignin occurred. Meanwhile, the peaks at 1089 cm −1 were attributed to the increase in the ether bonds, 50 due to condensation reactions between lignin molecules. 51 In the XPS analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the detection of Fe 3+ ions in acidic environments, C-SS-CDs have a 40% photoluminescence quantum yield in diluted acid solution. 58 3.14.5. Chitosan as a Supercapacitor.…”
Section: Effect Of Silica Quantity On Water Flow Rate Via Chitosan Me...mentioning
confidence: 99%
“…At present, the main methods of intelligently controlling the release of antifouling agents are pH response, enzyme response, and temperature response . Up to now, a variety of nanomaterials with good controlled-release properties have been reported, including poly­(vinyl alcohol) microspheres in a silk sericin-based hydrogel, composite films with an adjustable number of layers using sodium alginate (SA), chitosan (CS), and activated charcoal (AC), microcrystals, polyvinyl alcohol/chitosan microspheres, and a selenium-rich tea set. , Chitosan (CS) has antibacterial properties due to the interaction between its positively charged amino group and the negatively charged cell membrane of bacteria. , The nanocapsules made from CS exhibit typical pH response characteristics due to the large number of amino groups contained in the side chain. , In addition, the intelligent delivery of fungicides can be realized by the modification of chitosan. , Our research group has developed a capsaicin@chitosan (CAP@CS) microcapsule with pH response performance, which can realize the intelligent controlled release of the natural bactericide CAP, which plays an effective sterilization and antifouling role. , However, its dispersion is limited. In order to improve the dispersion on the basis of pH response sterilization, we hope to introduce other materials to further improve the performance of intelligent response controlled release sterilization. , Two-dimensional materials (graphene, covalent organic frameworks) have great potential for marine protective materials, such as corrosion protection and fouling protection, due to their excellent adsorption characteristics, mechanical strength, thermal stability, and other characteristics. , In recent years, 2D covalent organic frameworks (COFs), which are typical representatives of 2D nanomaterials, have the characteristics of diverse synthesis methods, large specific surface area, stable physical and chemical properties, and broad application prospects in different fields. , COF-MOF hybrid materials have ingenious and obvious structural characteristics and excellent performance .…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In addition, the intelligent delivery of fungicides can be realized by the modification of chitosan. 39,40 Our research group has developed a capsaicin@ chitosan (CAP@CS) microcapsule with pH response performance, which can realize the intelligent controlled release of the natural bactericide CAP, which plays an effective sterilization and antifouling role. 41,42 However, its dispersion is limited.…”
Section: Introductionmentioning
confidence: 99%